FINANCE AND ITS ROLE IN THE COUNTRY’S ECONOMY - Norboeva, D.J; Malikov , M.A (Educational Research in Universal Sciences, 2024)
This article analyzes finance, the importance of finance for the state, and what its tasks are. Also, information on state budget revenues and state budget expenditures was provided.